Perancangan Video Company Profile Badan Pengelolaan Pajak Dan Retribusi Daerah Kota Batam - Evita S.Tr.Kom; Dwi Ely Kurniawan (Politeknik Negeri Batam, 2021)
Badan Pengelolaan Pajak dan Retribusi Daerah (BP2RD) of Batam City is a government agency engaged in tax and retribution services. To maximize local tax and retribution services to the community, BP2RD Batam City requires information media facilities that can introduce agency assets as well as transparency of taxes and levies to leaders, other agencies, and taxpayers. The media will be made in the form of a video company profile. The method of data collection was carried out by means of field observations, interviews, and literature studies. based on the results of the test analysis by obtaining an average percentage value of 92.5%, where the proportion value falls into the good response scale category. Videos will be created using Adobe Premiere Pro cc 2015 software, Adobe After Effects CS6, and Filmora. After that, quantitative research will be carried out by interviewing respondents and it will be measured with an instrument in the form of a Guttman scale.